Haptic ambience: Ambient play, the haptic effect and co-presence in Pokémon GO. (February 2019) - Apperley, Thomas; Moore, Kyle
Haptic media studies emphasize the centrality of touch in the experience of digital media. This article considers how the haptic effect created by relationship between touch, gesture and spatial practice in Pokémon GO cements new possibilities for ambient play and co-presence. The app effectively draws on the genealogies of Nintendo's handheld Pokémon games, but through the shift to smartphone devices the app creates new forms of ambient play, co-presence and communication that are realized through the publicness of the touch, gesture and comportment which make up the haptic effect of the app. By making the smartphones camera an integral part the game, Pokémon GO suggests the wider relevance of the communicability of feeling and gesture by extending ambient play and co-presence into social media, allowing players to (re)-experience the feeling and touch of Pokémon GO through affective resonance. This suggests that the tactility and touch of the haptic affect are embedded in a matrix of embodied experiences that are revealed through how photography and social media become sites for extending and ambient play.